THE ONOMATOPOEIA IN ROBERT VENDETTI’S COMIC “THE FLASH” - Muin, Abd.; Rauf, Masykur; Hidayat, Amrullah Nur (Elite : English and Literature Journal, 2016)
Abstract This research studied about the onomatopoeia in Robert Vendetti’s comic “The Flash”. The aims of this research was to find the kinds of onomatopoeia that are used by the author in The Flash comics and to know the lexical and contextual meanings of those onomatopoeia words in The Flash comic. This research applied descriptive qualitative method where the data were analyzed through Bredin’s theory. The researcher found that there are twenty-nine Onomatopoeia words that applied in The Flash comic and there are some onomatopoeia words that has no lexical meaning and some contextual meaning are similar with the lexical meaning. The researcher concluded that most of onomatopoeia words that applied in The Flash comic is Direct Onomatopoeia and there are only two Associative Onomatopoeia that applied in The Flash comic. The implication of this research is to give more description and comprehending about onomatopoeia. Moreover, it can be a reference for the student of Adab and Humanities faculty who attracted to observe the similar research. Abstrak The Onomatopoeia in Robert Vendetti’s Comic “The Flash”. Penelitian ini belajar tentang onomatopoeia di Robert Vendetti komik "Flash". Tujuan dari penelitian ini adalah untuk menemukan jenis onomatopoeia yang digunakan oleh penulis dalam komik Flash dan mengenal makna leksikal dan kontekstual kata-kata onomatopoeia dalam komik Flash. Penelitian ini menerapkan metode kualitatif deskriptif yang mana data dianalisis melalui teori Bredin’s. Peneliti menemukan bahwa ada dua puluh sembilan Onomatopoeia kata yang diterapkan dalam komik Flash dan ada beberapa onomatopoeia kata-kata yang tidak ada artinya leksikal dan beberapa arti kontekstual sama dengan makna leksikal. Peneliti menyimpulkan bahwa sebagian besar kata-kata onomatopoeia yang diterapkan dalam komik Flash adalah Onomatopoeia langsung dan ada hanya dua Onomatopoeia asosiatif yang diterapkan dalam komik Flash. Implikasi dari penelitian ini adalah untuk memberikan keterangan lain dan memahami tentang onomatopoeia. Selain itu, dapat menjadi referensi untuk mahasiswa Fakultas Adab dan humaniora yang menarik untuk mengamati penelitian serupa.